Feasibility Study Of Reprocessed Acrylonitrile Butadiene Styrene (ABS) And Optimization Of Injection Moulding Parameters Via Taguchi Method - Ng, Chin Fei (2011)
To date, plastic manufacturers all over the world are burdened with environmental and waste management issues revolving around the efficient disposal of the post-industrial plastic waste. Tremendous efforts are aimed at facilitating the plastic recycling to a greater extent in accordance to the strict regulation of ISO 14001. In this research, usability of reprocessed acrylonitrile butadiene styrene (ABS) as substitute for virgin ABS was investigated by evaluating the effect of blending compositions of recycled ABS and reprocessing on tensile, rheological and morphological properties.